Kajian Aksiologi Pada Geguritan Bhiksuni - Ida Bagus Putu Eka Suadnyana (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2021)
Many literary works are buried in traditional libraries that have very high educational values. One of the works of Geguritan literature is a result of Balinese culture which is considered as something that can provide guidance or guidance in life. This includes traditional Balinese literary works in the form of Kidung and Geguritan. Geguritan Bhiksuni is one of the evidences for the Balinese people and as a mirror of traditional Balinese culture, although this Geguritan is not yet well known to lovers of Balinese literature, but in terms of content and quality it is not inferior to other Geguritan. On the other hand, this Geguritan really needs to be developed and disseminated to every member of the community so that it can be well understood and internalized by the contents and values contained in it. The theory used in solving this research problem is the Structural Theory used to analyze the structure of the nun's geguritan and the Value Theory is used to analyze the values of Hindu Religious Education in the nun's geguritan and the relevance of the value of Hindu Religious Education in the nun's geguritan to the world of education. This research is in the form of a descriptive qualitative design. This research is a study that examines the text. Data were collected using library techniques and critical reading techniques. After the data is collected then the data is analyzed through three stages, namely data reduction, data presentation, and drawing conclusions so that results are obtained that can solve problems. Based on the analysis, the conclusions of the research results are obtained, as follows; Hindu religious values contained in geguritan bhiksuni include Tattwa values and ethical values. Hindu religious values contained in geguritan bhiksuni are still relevant for the world of education today.Keywords: Values, Hindu Religion, Geguritan Bhiksuni